Answer:
or -116/9
Explanation:
Use algebraic manipulation:
Note: Remember, anything you do to one side of the equation you also do to the other side (e.g. +5 on one side, +5 on the other side).
First, multiply the whole equation by -1 to get the x to be positive so you get:
9x + 13 = -103
then subtract 13 from both sides:
9x = -103 - 13
9x = -116
then divide by 9:
x = -116/9
![x = -12(8)/(9)](https://img.qammunity.org/2023/formulas/mathematics/middle-school/oej6y84z7knr9qufw5xs8drls3pjm3lase.png)